RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB PADA SMK ISLAMIC CENTRE CIREBON - M. Agri Triansyah; Muhammad Farchan Mubarraq (Institut Pendidikan dan Bahasa Invada, 2020)
Learning media is a means of communication in the teaching and learning process in the form of hardware and software to achieve learning processes and outcomes effectively and efficiently, and can overcome the limitations of learning space and time. The purpose of this research is to design and produce a distance learning system product using raspberry pi as a portable server. The method used is the method of research and development (Research and Development) with the technique of observation, interviews and literature studies that are tailored to the needs of learning media in SMK Negeri 1 Cirebon. The test technique for this distance learning system uses the Black Box, namely testing is done by checking all statements in the program that are executed at least once and server testing is carried out by 30 students of industrial electronics engineering at SMK Negeri 1 Cirebon. The results of this study are a web server that runs on a raspberry pi 4 and can be accessed via a local or public network. The advantages of this tool are that it is cheaper than a server and is portable so that it can be moved from one place to another. The test results show that the server running on the raspberry pi 4 can function properly and can be implemented based on its purpose.